2020
DOI: 10.1093/bjc/azaa026
|View full text |Cite
|
Sign up to set email alerts
|

Benevolent Policing? Vulnerability and the Moral Pains of Border Controls

Abstract: In the United Kingdom, as in other jurisdictions, the language of vulnerability and ‘safeguarding’, protection and care is becoming increasingly prevalent, often dovetailing with punitive rationales and practices. Drawing from empirical material collected during a study on police–immigration partnership in everyday policing, the paper analyses how contemporaneous punitive and humanitarian turns in criminal justice are experienced by law enforcement officers doing border work on the ground and considers what im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 48 publications
0
42
0
Order By: Relevance
“…Research has confirmed that when established criminal-justice practices intersect with migration control, discretionary behaviour capitalises on the blurriness that ensues and can also create moral ambivalence on the part of individual officers implementing the policies (Aliverti 2020). Canadian research, for example, has found that policing migration at land borders and in everyday street policing is inevitably based on race, because officers have less background information to go on in the way that they might, for example, at airports.…”
Section: Discretion Policing and Border Policingmentioning
confidence: 99%
“…Research has confirmed that when established criminal-justice practices intersect with migration control, discretionary behaviour capitalises on the blurriness that ensues and can also create moral ambivalence on the part of individual officers implementing the policies (Aliverti 2020). Canadian research, for example, has found that policing migration at land borders and in everyday street policing is inevitably based on race, because officers have less background information to go on in the way that they might, for example, at airports.…”
Section: Discretion Policing and Border Policingmentioning
confidence: 99%
“…In general, detained men were denied vulnerability (see also Bhatia, 2020; Wyss and Fischer, 2021). Officers’ neglect of detained persons’ emotions demonstrates the racialised emotional stratification (Bonilla-Silva, 2019) at play in the camp, where prison officers’ suspicion and gut feelings about the people detained were considered sources of knowledge and reason (see also Aliverti, 2020). Indeed, the majority of officers insisted that their assessment about the racial classifications and inferiority was colourblind (see Parmar, 2018, who found similar patterns of justification among UK police officers).…”
Section: The Affective Infrastructures Of Ellebæk Detention Campmentioning
confidence: 99%
“…But in contrast to prisons, they confine people not for what they have done, but for who they are: namely, foreign and expellable 'others' (Bosworth, 2018). As such, they are sites of criminalisation (or 'crimmigration'; see Aas, 2013;Armenta, 2017), and exemplify how states expand and instrumentalise penal powers for the purpose of border and mobility control (Aliverti, 2012(Aliverti, , 2020Barker and Smith, 2021;Bosworth, Parmar, et al 2018). Detention camps are also junctions between penal power and border control, and function as technologies of citizenship (Walters, 2002) as they delineate the racial boundaries of membership (Bosworth, 2018;Bosworth, Franko, et al, 2018;Parmar, 2018).…”
Section: Racial Affect and The Making Of Expellable Othersmentioning
confidence: 99%
See 2 more Smart Citations